Vertical agriculture: Homestead horticulture suspended in sacks - WorldFish (2014)
Suspending horticulture in sacks above the ground can result in higher levels of productivity for vegetables when the challenges of unfertile or saline soil, flooding, waterlogging, and land and water constraints are regularly encountered.